Exploring Colonial Photographs Potential as a Historical Source on Reconstructing Buleleng Maritime History - Ahmad Ginanjar Purnawibawa; I Wayan Putra Yasa (Criksetra: Jurnal Pendidikan Sejarah, 2024)
Abstract: This article explores a possible way to use historical photographs archives and their untapped potential as invaluable historical sources. Focusing on the maritime history of Buleleng from 1920 to 1940 AD, this study explores the multifaceted digitized photos. These photos offer insights into the maritime landscape of Buleleng, shedding light on its pivotal role as a thriving center of maritime commerce and cultural exchange in Bali during the early 20th century. Through a visual history approach and critical analysis of a diverse range of photographs, this research shows the potential of photographs as historical sources to reconstruct the maritime past of Buleleng. The analysis in this article showed that historical photographs could provide varied information, such as different types of boats, commodities, activities, and daily life of people in the maritime-led life of Buleleng. Abstrak: Artikel ini mengeksplorasi tahapan dalam menggunakan arsip foto sejarah dan potensinya yang belum dimanfaatkan sebagai sumber sejarah yang sangat berharga. Sumber data yang digunakan dalam penelitian ini adalah foto-foto kolonial yang terkait dengan sejarah maritim Buleleng pada tahun 1920 hingga 1940 M. Foto-foto ini memberikan wawasan tentang lanskap maritim Buleleng, menyoroti peran pentingnya sebagai pusat perdagangan maritim dan pertukaran budaya yang berkembang di Bali pada awal abad ke-20. Melalui pendekatan sejarah visual dan analisis kritis terhadap foto-foto tersebut, penelitian ini menunjukkan potensi foto sebagai sumber sejarah untuk merekonstruksi sejarah maritim Buleleng. Analisis dalam artikel ini menunjukkan bahwa foto-foto sejarah dapat memberikan informasi yang beragam, seperti berbagai jenis perahu, komoditas, aktivitas, dan kehidupan sehari-hari masyarakat maritim Buleleng.